Materials management : an executive's supply chain guide - McDonald, Stan C., 1952- (Hoboken, N.J. : John Wiley & Sons, 2009)
"Drawing on author Stan McDonald's vast industry experience, Materials Management: An Executive's Supply Chain Guide presents you with a foundation to the basic methods and concepts used to successfully manage the flow of materials within your organization and throughout the supply chain. Its practical, user-friendly style will show you how to improve your company's operations as well as its bottom line."
"Materials Management shows you how to work smart and avoid common problems through best- and worst-case studies with sneak peeks into the "inner workings" of the materials process. Explaining the impact that inadequate inventory control has on a company and how these poor controls can reduce production, cause inefficiencies in labor, create excessive inventory, and increase freight expenses, this resourceful book prepares your company to become best-in-class. Its strategies, solutions, and technologies that keep your company financially viable and competitive in our ever-changing global economy."--Jacket
Ch. 1. Before Computer Systems -- Ch. 2. Material Requirements Planning -- Ch. 3. The Raging Fire and Firefighting -- Ch. 4. A Strong, Well-Balanced Materials Organization -- Ch. 5. General Review of Materials Practices -- Ch. 6. Lead Time -- Ch. 7. Inventory Accuracy -- Ch. 8. Cycle Counting -- Ch. 9. Releases to Suppliers -- Ch. 10. Planning Parameters -- Ch. 11. Electronic Data Interchange -- Ch. 12. Materials Control Graphs and Reports -- Ch. 13. Obsolescence -- Ch. 14. Physical Inventories -- Ch. 15. Receiving -- Ch. 16. Shipping -- Ch. 17. Carrier Selection -- Ch. 18. Supplier Selection and Ratings -- Ch. 19. Production -- Ch. 20. Best Materials Control Effort -- Ch. 21. Advanced Logistics Planning -- App. A. Mexican Plants -- App. B. Management Philosophies -- App. C. Color Code Management Styles.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Business logistics -- Management; Material requirements planning; Inventory control; Logistique (Organisation) -- Gestion; Planification des besoins en composants; Gestion des stocks; inventorying; TECHNOLOGY & ENGINEERING -- Industrial Technology; TECHNOLOGY & ENGINEERING -- Industrial Engineering; BUSINESS & ECONOMICS -- Production & Operations Management; Business logistics -- Management; Inventory control; Material requirements planning; dissertations; Academic theses; Academic theses; 2